Green Synthesis of Silver Nanoparticles and Their Bactericidal and Antimycotic Activities against Oral Microbes - Rodríguez Luis, Osvelia Esmeralda; Hernández Delgadillo, René; Sánchez Nájera, Rosa Isela; Martínez Castañón, Gabriel Alejandro; Niño Martínez, Nereyda; Sánchez Navarro, María del Carmen; Ruiz, Facundo; Cabral Romero, Claudio (2016)
Nanotechnology is a new discipline with huge applications including medicine and pharmacology industries. Although several methods and reducing agents have been employed to synthesize silver nanoparticles, reactive chemicals promote toxicity and nondesired effects on the human and biological systems. The objective of this work was to synthesize silver nanoparticles from Glycyrrhiza glabra and Amphipterygium adstringens extracts and determine their bactericidal and antimycotic activities against Enterococcus faecalis and Candida albicans growth, respectively. 1 and 10 mM silver nitrate were mixed with an extract of Glycyrrhiza glabra and Amphipterygium adstringens. Green silver nanoparticles (AgNPs) were characterized by TEM, VisNIR, FTIR, fluorescence, DLS, TGA, and X-ray diffraction (XRD) analysis. Bactericidal and antimycotic activities of AgNPs were determined by Kirby and Bauer method and cell viability MTT assays. AgNPs showed a spherical shape and average size of 9 nm if prepared with Glycyrrhiza glabra extract and 3 nm if prepared with Amphipterygium adstringens extract. AgNPs inhibited the bacterial and fungal growth as was expected, without a significant cytotoxic effect on human epithelial cells. Altogether, these results strongly suggest that AgNPs could be an interesting option to control oral biofilms.